THE ECONOMIC CONTENT, ESSENCE AND CLASSIFICATION OF THE CONCEPT OF LONG-TERM ASSETS: https://doi.org/10.5281/zenodo.15382439 - Safarov , Otabek (Journal of Contemporary World Studies, 2025)
This article discusses the relationship and differences between the international financial reporting standard (IFRS 38 Intangible Assets) and the national accounting standard (IFRS 7 Intangible Assets) used in asset accounting. These aspects will be discussed in the coverage of the topic. The concept of long-term assets, their economic nature, classification, and impact on the financial position of an enterprise are covered. The importance of their correct accounting is also analyzed.